2021
DOI: 10.1142/s0219091521500144
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Uncertainty and Stock Market Uncertainty: Some Further Evidence From Pakistan

Abstract: The paper provides an updated evidence of the linkage between stock market and macroeconomic factors in Pakistan. The sample period is from January 2011 to November 2017. Macroeconomic variables used are money supply, exchange rate, treasury bill rate, inflation and industrial production. Generalized autoregressive conditional heteroscedasticity (GARCH) models have been used to examine the impact of macroeconomic factors on stock market return and stock market volatility. Findings suggest that macroeconomic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Whereas, IPI and FDI Granger cause KSE unidirectionally and KSE Granger cause BS. The overall result regarding IPI granger cause KSE is supported by earlier research regarding the linkage between macroeconomic factors and the stock market in Pakistan from 2011 to 2017 revealed that industrial production positively impacts the fluctuations of stock market returns (Aziz et al, 2021). The results also reveal that interest rate is used as an important tool of monetary policy, which has a significant short-run impact on stock returns during COVID.…”
Section: Granger-causality Testssupporting
confidence: 65%
See 2 more Smart Citations
“…Whereas, IPI and FDI Granger cause KSE unidirectionally and KSE Granger cause BS. The overall result regarding IPI granger cause KSE is supported by earlier research regarding the linkage between macroeconomic factors and the stock market in Pakistan from 2011 to 2017 revealed that industrial production positively impacts the fluctuations of stock market returns (Aziz et al, 2021). The results also reveal that interest rate is used as an important tool of monetary policy, which has a significant short-run impact on stock returns during COVID.…”
Section: Granger-causality Testssupporting
confidence: 65%
“…A study conducted on the impact of macroeconomic factors on stock return in the Nigerian stock market from 1998 to 2019 has found that industrial production has a positive and significant impact on stock return (Pole & Cavusoglu, 2021). Moreover, another research regarding the linkage between macroeconomic factors and the stock market in Pakistan from 2011 to 2017, also revealed that industrial production positively affects the fluctuations of stock market returns (Aziz, Marwat, & Mustafa, 2021).…”
Section: Interest Rate Bank Spread Industrial Production and Stock Re...mentioning
confidence: 97%
See 1 more Smart Citation
“…The cumulative amount of green loans from 21 significant Chinese banks reached US $1.69 trillion by the end of 2020, demonstrating the consistent and long-term advancement of Chinese businesses in their transition to becoming green and sustainable. Economic policy uncertainty leads to fluctuations in financial markets [ 12 ]. In order for businesses to accomplish high-quality transformation and sustainable development in an uncertain environment, green innovation is a crucial internal driving factor [ 13 ].…”
Section: Introductionmentioning
confidence: 99%